'Fighting an uphill battle': a qualitative study of the challenges encountered by pharmacy workers when providing services to men who have sex with men in Dar es Salaam, Tanzania - Joakim Öhman; Markus Larsson; John Kashiha; Anette Agardh (Taylor & Francis Group, 2020)
Background Previous research suggests that Tanzanian MSM might prefer consulting pharmacies and drugstores, rather than public healthcare services, when in need of STI medicines and treatment. Yet, few studies have explored the experiences of providing services to MSM clients among those working at pharmacies and drugstores and examined what challenges they encounter in providing these services. Objective To gain increased knowledge and understanding of the perceived challenges encountered by pharmacists and drugstore workers when providing STI services to MSM clients in Dar es Salaam, Tanzania. Method In early 2016, 16 semi-structured interviews were conducted with persons working at private pharmacies and drugstores in Dar es Salaam. Data were interpreted through qualitative content analysis. Results The overarching theme that emerged was labelled 'Fighting an uphill battle', which reflected the challenges pharmacy workers experienced during interactions with MSM clients, and in particular service provision. Pharmacy workers tried to act upon the best of their knowledge to meet the needs of clients, given their understanding of risks and obstacles that MSM faced. Yet, the lack of educational and professional preparedness and insufficient financial and human resources, regarded as necessary to meet the needs of a stigmatised client group, formed barriers for effective service delivery. Conclusions In order to support pharmacists and drug-store workers in Tanzania to address perceived challenges for service delivery to MSM clients, systematic and continuous training on MSM's sexual health is required. Furthermore, inter-professional cooperation that harnesses provider involvement from all tiers in the healthcare system is essential to offer complementary services to ensure proper STI care and treatment. Thus, interventions that focus on inter-professional communication and interaction between pharmacists and physicians could have a positive impact on timely referrals of suspected STI cases among marginalised populations.